IbM KELOMPOK USAHA PEMBESARAN AYAM BURAS DI DESA PENGARON KECAMATAN PENGARON KABUPATEN BANJAR KALIMANTAN SELATAN - Siti Erlina; Ilhamiyah Ilhamiyah (Universitas Islam kalimantan MAB, 2018)
The productivity of Chicken in two groups of partners (Kindai Limpar and Harapan Masa) in Pengaron Sub-district, Banjar Regency, South Borneo, is still low. This is due to the lack of knowledge about the management of breeders of good and correct Chicken care and the inability of farmers to buy a tool for the beak (debeaker), because the price is very expensive and only outside of South Borneo. In addition, knowledge of effective and efficient marketing strategies is still lacking. Therefore, Science and Technology Program for the Community is very necessary to overcome these problems. The target audience of this program is a society that has not been economically productive but has a strong desire to become an entrepreneur. Outcome targets are services and Technology / tools / products / goods. The method used is counseling and demonstration. Both groups of Partners get knowledge through counseling and technology transfer in the form of cutting tool part (debeaker) in a special modification, simple and cheap (modified debeaker from the team proposer). In this counseling activity breeders are given maintenance ways to start seedling, seed selection, cage, feeding, drinking, beak cutting techniques, pest control and chicken livestock disease (vaccine feeding technique), maintenance techniques of Chicken Buras start zero days until with three weeks and maintenance techniques of Chicken Buras age three weeks up to the age of eight weeks. In addition, the two partner groups are assisted by the provision of partial modification tools (debeaker) of the team as well as informed on how to use the tool and partners are also given knowledge about the marketing strategy of effective and efficient domestic poultry. Based on the results of the activities of IbM it can be seen that the participants / partners IbM very interested and enthusiastic with the activities of this IbM. This activity can open the insight of breeders, improve knowledge and skills of breeders in breeding chickens males with better technology implementation and correct, so it can overcome the problems faced by farmers so far and will ultimately increase the income and welfare breeders